High Altitude Weather Station Data at USGS Benchmark Glaciers ... - U.S. Geological Survey Benchmark Glacier Program; Emily H Baker; Erich H Peitzsch; Louis Sass; Zachary S Miller; Erin N Whorton (U.S. Geological Survey, 2019)
Since the late 1950s, the USGS has maintained a long-term glacier mass-balance program at three North American glaciers. Measurements began on South Cascade Glacier, WA in 1958, expanding to Gulkana and Wolverine glaciers, AK in 1966, and later Sperry Glacier, MT in 2005. Additional measurements have been made on Lemon Creek Glacier, AK to compliment data collected by the Juneau Icefield Research Program (JIRP; Pelto et al., 2013). Direct field measurements are combined with weather data and imagery analyses to estimate the seasonal and annual mass balance at each glacier in both a conventional and reference surface format (Cogley and others, 2011). High-altitude measurements of meteorological data have been collected since the beginning of the USGS Benchmark Glacier Program adjacent to glaciers in order to support related science. This portion of the data release includes select weather data that has received basic quality control and assurance. Data is released at three different levels of processing, ...